Comparative Phylogeography of Direct-Developing Frogs (Anura: Craugastoridae: Pristimantis) in the Southern Andes of Colombia - García-R, Juan C.; Crawford, Andrew J.; Mendoza, Ángela María; Ospina, Oscar; Cardenas, Heiber; Castro, Fernando (PLOS ONE, 2012)
The Andes of South America hosts perhaps the highest amphibian species diversity in the world, and a sizable component of that diversity is comprised of direct-developing frogs of the genus Pristimantis (Anura: Craugastoridae). In order to better understand the initial stages of species formation in these frogs, this study quantified local-scale spatial genetic structuring in three species of Pristimantis. DNA sequences of two mitochondrial gene fragments (16S and COI) were obtained from P. brevifrons, P. palmeri and P. jubatus at different locations in the Cordillera Occidental. We found high levels of genetic diversity in the three species, with highly structured populations (as measured by FST) in P. brevifrons and P. palmeri while P. jubatus showed panmixia. Large effective population sizes, inferred from the high levels of genetic diversity, were found in the three species and two highly divergent lineages were detected within P. jubatus and P. palmeri. Estimated divergence times among populations within P. brevifrons and P. palmeri coincide with the Pleistocene, perhaps due to similar responses to climatic cycling or recent geological history. Such insights have important implications for linking alpha and beta diversity, suggesting regional scale patterns may be associated with local scale processes in promoting differentiation among populations in the Andes.